2015
DOI: 10.1016/j.jmb.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Organization Changes and the Epigenetic Silencing of FLC during Vernalization

Abstract: Changes in nuclear organization are considered an important complement to trans-acting factors, histone modifications and non-coding RNAs in robust and stable epigenetic silencing. However, how these multiple layers interconnect mechanistically to reinforce each other's activity is still unclear. A system providing long timescales facilitating analysis of these interconnections is vernalization. This involves the Polycomb-mediated epigenetic silencing of flowering locus C (FLC) that occurs as Arabidopsis plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 109 publications
1
20
0
Order By: Relevance
“…Although we cannot exclude that expression of the LTR AtGP1 transgene could also be controlled by trans-acting factors superimposing RdDM-based repression, two-layered silencing has nonetheless been identified using mutant plants for the Morpheus' molecule1 (MOM1) putative helicase (70,71) and for the MORC ATPase (72), which are both believed to be involved in DNA or chromosomal remodeling processes. Based on these findings, it is possible that some heterochromatin loci might be sensitive to a position-dependent or condensation-dependent regulatory control during cotyledon development, a process that may relate to the observed relationship between chromatin-based repression and subnuclear positioning of multicopy transgenes (73) and of the FLC gene (66,74). Future studies aimed at dissecting nuclear architectural changes during photomorphogenesis should allow an assessment of the functional impact of heterochromatin organization and genome topology structuration on the reprogramming of gene expression.…”
Section: Discussion Nuclear Rearrangements and Increased Transcriptiomentioning
confidence: 99%
“…Although we cannot exclude that expression of the LTR AtGP1 transgene could also be controlled by trans-acting factors superimposing RdDM-based repression, two-layered silencing has nonetheless been identified using mutant plants for the Morpheus' molecule1 (MOM1) putative helicase (70,71) and for the MORC ATPase (72), which are both believed to be involved in DNA or chromosomal remodeling processes. Based on these findings, it is possible that some heterochromatin loci might be sensitive to a position-dependent or condensation-dependent regulatory control during cotyledon development, a process that may relate to the observed relationship between chromatin-based repression and subnuclear positioning of multicopy transgenes (73) and of the FLC gene (66,74). Future studies aimed at dissecting nuclear architectural changes during photomorphogenesis should allow an assessment of the functional impact of heterochromatin organization and genome topology structuration on the reprogramming of gene expression.…”
Section: Discussion Nuclear Rearrangements and Increased Transcriptiomentioning
confidence: 99%
“…Many studies have reported the involvement of histone modifications in regulating the expression of FLC and MAFs (AusĂ­n et al, 2004;Kim et al, 2004;Sung and Amasino, 2004;Greb et al, 2007;Jiang et al, 2008Jiang et al, , 2009Buzas et al, 2011;He, 2012;JĂ©gu et al, 2014;Shen et al, 2014;Zhu et al, 2015). Posttranslational modifications of RNA polymerase II components, whose recruitment is mediated by TOP1a, also contribute to histone modifications as transcription proceeds (Egloff and Murphy, 2008;Spain and Govind, 2011).…”
Section: Top1a Affects Histone Modifications At Flc Maf4 and Maf5 Locimentioning
confidence: 99%
“…SWI/SNF chromatin-remodelling complex BAF60 seems to be required for the formation of the FLC gene loop and the disruption of the loop seems to facilitate enhanced COOLAIR expression during cold. Zhu et al (2014) observed in addition a more long-range restructuring of chromatin in the FLC context. They visualised in vivo position of lacO-tagged FLC via YFP-LACI and could show a condensation of FLC during vernalisation indicating a physical clustering.…”
Section: Chromatin Structure At Flcmentioning
confidence: 79%